Creating a One-Stop-Shop for Automobile Solutions in Kolkata, India. - Kanoria, Shrivardhan (2009)
This is a research lead business plan concerning making a one-stop-shop for automobile solutions in Kolkata, India, containing three elements of business. Firstly, it would involve restoration, buying and selling of vintage and classic cars. Secondly, it would contain modern car customisation. Thirdly, it would contain modern car servicing, buying and selling. These would be the core activities, having associates non core businesses as well.